Exploring the alternative assessment on mathematical instruction in an era of uncertainty - Muhammad Naim Mahmud; Heri Retnawati; Eri Yusron; Elita Rachmayanti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
The impact of the Covid-19 pandemic in education has caused the learning curriculum to experience replication. Not only in delivering learning material, but replication also occurs in the learning assessment process. Teachers are required to be able to carry out an objective assessment of learning in all subjects. This study aims to determine teacher difficulties and explore alternative assessments used by teachers in mathematics learning in the pandemic era. This research is a qualitative study using an exploratory study approach that aims to deepen the study of research objectives that focus on constraint and alternative phenomena in assessing mathematics learning in elementary schools. The instrument used has been validated by experts and got the value of the coefficient Aiken = 0,742 this shows that the instrument used is valid and in the good category. Data collection was carried out through questionnaires for teachers and field observations in the online learning process. Data analysis was carried out by using descriptive techniques from the findings of the questionnaire and observation instruments. This study's results reveal that the teacher finds it difficult to provide an objective assessment of learning, and the alternative assessment of mathematics learning used is digital learning assessment and structured assignments to parent representatives in each zoning. Future research is expected to develop assessment instruments that can facilitate online learning assessments in the pandemic era.